2020
DOI: 10.7150/ijms.46581
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of powdered product of Bu Yang Huan Wu decoction: Possible role in protecting against Transient Focal Cerebral Ischemia

Abstract: Bu Yang Huan Wu decoction (BYHW) is a traditional Chinese medicine (TCM) that consists of several herbs and has been used in patients with ischemic stroke for centuries. Although powdered formula of BYHW has widely been prescribed in clinic nowadays, evidence-based effectiveness and mechanism of action of BYHW powdered product in stroke remain to be characterized. Adult male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO) for 90 min followed by reperfusion for 24 h (ischemia/reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…One metaanalysis that assessed 56 studies with 1270 animals indicated a substantial neuroprotective action from BYHW decoction in models of focal cerebral ischemia [48]. The possible mechanism involved anti-inflammation [22], antioxidation [49], regulation of VEGF or angiopoietin-1 expression [50,51], and improvement of synaptic plasticity [52]. Clinical studies have also proved the effectiveness of BYHW decoction on stroke [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One metaanalysis that assessed 56 studies with 1270 animals indicated a substantial neuroprotective action from BYHW decoction in models of focal cerebral ischemia [48]. The possible mechanism involved anti-inflammation [22], antioxidation [49], regulation of VEGF or angiopoietin-1 expression [50,51], and improvement of synaptic plasticity [52]. Clinical studies have also proved the effectiveness of BYHW decoction on stroke [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…The Bu Yang Huan Wu (BYHW) decoction has been widely used in China to treat stroke and stroke-related diseases since the 17 th century. It is one of the most frequently prescribed medications for ischemic or hemorrhagic stroke in China [22][23][24][25]. One study reported that BYHW decoction, in combination with cholinesterase inhibitor donepezil, which is a medicine used to treat Alzheimer's disease, improved cognitive function in stroke patients in the clinic [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, the roles of Rpl18, Eif3c, Rhoc, Gng13, and Gng10 in IS have not been reported. Studies have shown that BYHW, NXT, and YYTN inhibit the inflammatory factors [ 52 , 53 ]. Any of the factors discussed above may be relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Z et al, 2019 ). In the study by Chen K. Y. et al (2020) , the authors reveal that BHT powdered product exhibited therapeutic efficacy for experimental stroke via reducing the expressions of TNF-α and IL-6 and increasing the expressions of TGF-β and IL-10. To explore the BHT effects on angiogenesis and neuroprotection after CI/RI, some researchers made H 2 O 2 /R-induced oxidative stress in human umbilical vein endothelial cells (HUVECs) and MCAO/R-induced rats.…”
Section: Chm Formulations For CImentioning
confidence: 99%